2020
DOI: 10.1007/s12639-020-01262-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic significance of C-reactive protein and hematological parameters in acute toxoplasmosis

Abstract: Toxoplasmosis is a zoonosis caused by Toxoplasma gondii, which can be acquired by oral contact and may cause severe health problems especially for pregnant (congenital toxoplasmosis) and immunocompromised patients. This study aimed to verify the diagnostic significance of hematological parameters and C-reactive protein (CRP) for toxoplasmosis acute detection. A case-control study was carried out between December 2017 and May 2018, in samples of convenience independent of age and sex. The case group was formed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…CRP values can vary in ehrlichiosis, legionnaires’ disease, and rabies infection, whereas evidence on fungal coccidioidomycosis seems contrasted since low CRP values have been reported in immunocompetent cases—yet, such low values may have occurred due to the immunocompromised state [ 1013 , 1014 , 1015 , 1016 , 1017 , 1018 , 1019 ]. Data on toxoplasmosis, again, vary, as significantly high CRP values have been reported after infection, but a study revealed no significant difference between cases and controls [ 1020 , 1021 ]. Increased CRP values have also been reported in the acute phase of cholera, as seen in old literature data [ 1022 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…CRP values can vary in ehrlichiosis, legionnaires’ disease, and rabies infection, whereas evidence on fungal coccidioidomycosis seems contrasted since low CRP values have been reported in immunocompetent cases—yet, such low values may have occurred due to the immunocompromised state [ 1013 , 1014 , 1015 , 1016 , 1017 , 1018 , 1019 ]. Data on toxoplasmosis, again, vary, as significantly high CRP values have been reported after infection, but a study revealed no significant difference between cases and controls [ 1020 , 1021 ]. Increased CRP values have also been reported in the acute phase of cholera, as seen in old literature data [ 1022 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…The presence of cancer in this procedure is regression process, the techniques and algorithms are based on a model design in new machine learning. In the proposed model the unseen data provides a good exact result on testing stages [20]. The main three stages of machine learning that will be applied to available datasets are preprocessing of data, selection of features or its extraction, and classification [21].…”
Section: Survivor Of Cancermentioning
confidence: 99%